Protective role of perivascular adipose tissue in the cardiovascular system - Tong, Yi; Zuo, Zheng; Li, Xinqi; Li, Minghua; Wang, Zhenggui; Guo, Xiaoxue; Wang, Xishu; Sun, Ying; Chen, Dongmei; Zhang, Zhiguo (Frontiers in Endocrinology, 2023)
This review provides an overview of the key role played by perivascular adipose tissue (PVAT) in the protection of cardiovascular health. PVAT is a specific type of adipose tissue that wraps around blood vessels and has recently emerged as a critical factor for maintenance of vascular health. Through a profound exploration of existing research, this review sheds light on the intricate structural composition and cellular origins of PVAT, with a particular emphasis on combining its regulatory functions for vascular tone, inflammation, oxidative stress, and endothelial function. The review then delves into the intricate mechanisms by which PVAT exerts its protective effects, including the secretion of diverse adipokines and manipulation of the reninangiotensin complex. The review further examines the alterations in PVAT function and phenotype observed in several cardiovascular diseases, including atherosclerosis, hypertension, and heart failure. Recognizing the complex interactions of PVAT with the cardiovascular system is critical for pursuing breakthrough therapeutic strategies that can target cardiovascular disease. Therefore, this review aims to augment present understanding of the protective role of PVAT in cardiovascular health, with a special emphasis on elucidating potential mechanisms and paving the way for future research directions in this evolving field.